2019
DOI: 10.1177/0022185619834320
|View full text |Cite
|
Sign up to set email alerts
|

Unions and collective bargaining in Australia in 2018

Abstract: There is a storm brewing over the roles of unions and collective bargaining in Australian employment relations. Unions, frustrated with what they see as practical and legislative restrictions on protection of workers’ rights, seek to ‘change the rules’. Employers, on the other hand, have been successful in restricting or rolling back bargaining rights, supported by their associations, the Coalition government and an assertive interpretation of the Fair Work Act. Add to this the impending federal election and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The number of NUCAs fluctuated within a narrow range between 22.4 and 32.5% of all agreements, with an average annual rate of 27.1%. This suggests their incidence followed similar trends to union agreements (see Bray et al., 2019). There were greater variations over time in the employees covered, ranging from a high for NUCAs of 14.9% in 2015 to a low of 3.8% in 2018.…”
Section: The Incidence and Coverage Of Nucasmentioning
confidence: 53%
See 1 more Smart Citation
“…The number of NUCAs fluctuated within a narrow range between 22.4 and 32.5% of all agreements, with an average annual rate of 27.1%. This suggests their incidence followed similar trends to union agreements (see Bray et al., 2019). There were greater variations over time in the employees covered, ranging from a high for NUCAs of 14.9% in 2015 to a low of 3.8% in 2018.…”
Section: The Incidence and Coverage Of Nucasmentioning
confidence: 53%
“…6306.0), which estimates the proportion of Australian employees whose wages are mostly set by collective agreements. As has been revealed many times, this source consistently suggested that around 40% of employees in Australia relied on collective agreements to set their pay in the years between 2002 (when the survey was first conducted) and 2016, although most recent results in 2018 see a slight decline (Bray et al., 2019). However, this source of data makes no distinction between the coverage of union agreements and non-union collective agreements.…”
Section: The Incidence and Coverage Of Nucasmentioning
confidence: 88%
“…Labor’s leader, Bill Shorten, a former senior union official, dedicated his campaign policy and rhetoric to significantly reducing inequality, by levelling up (and also somewhat down), both in workplaces and more broadly. Here, his policies linked with those of the Australian Council of Trade Unions (ACTU), itself with a leadership now more committed to mobilising and campaigning (Bray et al., 2019).…”
Section: State and Federal Elections And The Politics Of Irmentioning
confidence: 99%
“…Negotiations between Alcoa and the AWU over a new enterprise agreement covering five sites in the Western Australian alumina industry , which were reported in last year’s review (Bray, Macneil and Spiess, 2019: 368), continued with equal drama during 2019. After 2 years of negotiations, an extended strike and failed ballots for proposed enterprise agreements (EAs), the company’s application for the termination of the agreement was accepted by the FWC, but the AWU appealed.…”
Section: Collective Bargaining and Collective Agreement Makingmentioning
confidence: 99%
“…In December, a surprise third discussion paper appeared focusing on ‘cooperative workplaces’, calling for submissions from interested parties by the end of February 2020 (AGD, 2019c). Given the issues raised in the Discussion Paper (Bray, Macneil and Stewart, 2019), the rapid support received from employers (Marin-Guzman, 2019b) and the government’s general approach towards industrial relations, this appears to be an exercise focused exclusively on management practices rather than an attempt to improve relationships with unions. But time will tell.…”
Section: Public Policy Unions and Collective Bargainingmentioning
confidence: 99%